Fuzzy topologies generated by fuzzy relations - Mishra S.; Srivastava R. (My University, 2025)
In this paper, we have introduced and studied fuzzy topologies generated by fuzzy relations. Several related results have been proved. In particular, we have obtained characterizations of a fuzzy topology generated by a fuzzy relation, a fuzzy topology generated by a fuzzy interval order, a preorderable fuzzy topology and an orderable fuzzy topology. We have also introduced and studied fuzzy bitopological spaces generated by fuzzy relations. © 2016, Springer-Verlag Berlin Heidelberg.